Edukasi Pengaruh pH Media dan Lama Fermentasi Terhadap Basil Nata de Coco - Mustam, Mariaulfa; Azis, Hijrah Amalia; Arfa, Arfa (Universitas Patria Artha, 2021)
Nata is one of the organic food products that has a high fiber content. Nata is a product of fermentation by Acetobacter xylinum. The review that discusses the making of nata by analyzing the effect of the pH of the media and the duration of fermentation at the same time is still very limited. Thus, this review aims to discuss the effect of media pH and fermentation time on nata de coco bacilli. Paying attention to the factors that affect the growth of Acetobacter xylinum bacteria during the fermentation process needs to be done so that it can produce nata de coco with optimum thickness and weight and a chewy texture. These factors include the pH of the media and the length of fermentation. The ingredients for making nata de coco consist of coconut water, granulated sugar, ZA or Ammonium phosphate, and Acetobacter xylinum seeds. The method of implementing the activity which consists of counseling and practice of making nata de coco is able to increase the knowledge of residents, teachers, students (i) about nata de coco and coconut water which are potential natural plants (natural products), as well as skills (soft skills) in making nata de coco. The teachers, students(i) and residents admitted that they were greatly helped by this activity as a form of training that could be applied in their daily lives in entrepreneurship, even though it was a small scale.Keyword: nata de coco, media pH, fermentation time, education